Identify Normative Values of Balance Tests Toward Neurological Assessment of Sports Related Concussion - Samaneh Eimanipure (Iranian Rehabilitation Journal, 2012)
Objectives: Deterioration in postural control mechanisms is termed postural instability and results increased postural sway and many laboratory techniques and instruments are characterized by a wide range of neurological signs and symptoms to the medical management. Thus the current study designed to assess the reliability of commonly used clinical measures of balance and determined normal values. Also, the second purpose was scrutiny of effect age, length weight and body mass index (BMI) on perform clinical balance tests.